Characterization of p-type multicrystalline silicon prepared by cold crucible continuous melting and directional solidification. (September 2017) - Huang, Feng; Chen, Ruirun; Guo, Jingjie; Ding, Hongsheng; Su, Yanqing
Abstract: A solar-grade boron doped silicon ingot with the cross section of 62 mm× 62 mm was cast by cold crucible continuous melting and directional solidification (CCDS). The characterization of this p-type multicrystalline silicon (mc-Si) was measured and evaluated. The results indicate that the ingot mainly consists of uniform columnar grains preferentially aligned parallel to the ingot growth direction. The average density of dislocations ( N dis ) in the center area varies from 4 × 10 4  cm −2 to 4 × 10 5  cm −2, and it is much lower than that in the peripheral area. Comparing with the raw material, the oxygen concentration in the cast ingot is much lower while the carbon holds the same level. The electrical resistivity distributes uniformly and its average value is same as that of the raw material. The minority carrier lifetime (MCLT) is higher than that of the raw material and no region with obvious low MCLT is observed. CCDS has shown to be a potential process to produce mc-Si for solar cells with no crucible contamination and consumption, high production efficiency and uniform quality.